The Relationship Among Parenting Practice Creativity and Parents Mental Health With Intelligence Quotient and Behavioral Disorder of 7-8 Years Old Children in Qaemshahr City - Hassanli, Nastaran (International Clinical Neuroscience Journal, 2019)
Background: The aim of this study was the survey of the relationship of parenting practice, creativity and parent’s mental health with intelligence quotient and behavioral disorder of 7-8 years old children in Qaemshahr city. Methods: In this cross-sectional descriptive-analytical study. The statistical population consisted of seven and eight years old children in Qaemshahr city in 2017. Three hundred children among them selected with stratified random sampling. Data gathered by Baumrind parenting practices questionnaire, Thurstone and Mellinger creativity questionnaire, Derogatis mental health, Wechsler intelligence scale for children and Rutter children’s behavioral disorder. Data analysis executed by one-way ANOVA test and Pearson correlation with SPSS 22. Results: The results showed that there is no significant difference between behavioral disorder rate of boys & girls (P < 0.05). Also, there is the significant relationship among parenting practices with intelligence quotient and children behavioral disorder (P < 0.05), while there was no significant relationship between intelligence quotient and children’s behavioral disorder with creativity (P < 0.05). Moreover, there was a significant relationship between mental health with behavioral disorder among children (P < 0.05), however, there was no significant relationship with intelligence quotient (P < 0.05). Conclusion: According to research results we can conclude that welfare and educational equipment’s by short-term, medium-term and long-term planning may enhance health and mental comfort among families with their children’s behavioral disorders.